The glucocorticoid receptor in brown adipocytes is dispensable for control of energy homeostasis - Glantschnig, Christina; Nawroth, Peter Paul; Herzig, Stephan (EMBO reports, 2019)
Abstract: Aberrant activity of the glucocorticoid (GC)/glucocorticoid receptor (GR) endocrine system has been linked to obesity-related metabolic dysfunction. Traditionally, the GC/GR axis has been believed to play a crucial role in adipose tissue formation and function in both, white (WAT) and brown adipose tissue (BAT). While recent studies have challenged this notion for WAT, the contribution of GC/GR signaling to BAT-dependent energy homeostasis remained unknown. Here, we have generated and characterized a BAT-specific GR-knockout mouse (GRBATKO), for the first time allowing to genetically interrogate the metabolic impact of BAT-GR. The HPA axis in GRBATKO mice was intact, as was the ability of mice to adapt to cold. BAT-GR was dispensable for the adaptation to fasting?feeding cycles and the development of diet-induced obesity. In obesity, glucose and lipid metabolism, insulin sensitivity, and food intake remained unchanged, aligning with the absence of changes in thermogenic gene expression. Together, we demonstrate that the GR in UCP1-positive BAT adipocytes plays a negligible role in systemic metabolism and BAT function, thereby opposing a long-standing paradigm in the field.